ANALGESIC EFFECT OF CAUDAL AND ILIOINGUINAL NERVE BLOCKADE AMONG CHILDREN UNDERGOING INGUINAL SURGERIES (Journal of Medical & Health Sciences Review, 2025)
BACKGROUND: Pain management in the pediatric patients undergoing inguinal surgeries during postoperative period is of paramount importance to facilitate smooth recovery and to minimize complications. Caudal blocks (CB) and ilioinguinal nerve blocks (IINB) are types of regional anesthesia that are commonly used to achieve this. Even though both have an appropriate analgesic effect, the possible adverse effects, including motor blockade and urinary retention highlight the need to compare their efficacy and safetyOBJECTIVE: To compare the analgesic effects of caudal blocks and IINB in children undergoing inguinal surgeries.PATIENTS AND METHODOLOGY: This quasi-experimental research was carried out between August 2023 and August 2024 at the Department of Pediatric Surgery, Rawalpindi Medical University, Rawalpindi, and it must be acknowledged that it was approved by RMU Ethical Review Board. There were 60 pediatric patients recruited between 1-12 years old undergoing elective inguinal hernia repair or orchidopexy. Using MedCalc software, the sample size was calculated at a 95 percent confidence level and 80 percent power. Non-random consecutive sampling was adopted and patients were considered random and divided into two groups, i.e., Group A (Caudal Block) and Group B (IINB) with 30 patients each. Preoperative administration of analgesic methods was done under sterile conditions. Children under the age of 4 years were evaluated with the FLACC scale whereas those above 4 years were evaluated with NRS. Some of the prime outcomes were the duration of analgesia and the intensity of pain; the secondary outcomes were the cumulative consumption of analgesic and the occurrence of complications like motor block, urinary retention, and postoperative nausea and vomiting (PONV).RESULTS: 60 pediatric patients; with a mean age of 5.98 ± 2.28 years were included in the study. There were 81.7% male participants. At all postoperative periods, the IINB group reported substantially lower pain scores than the caudal block group, with p-values of 0.006, 0.002 and 0.001 at the 1st, 2nd and 3 rd intervals, respectively. The IINB group had also a mean duration of analgesia of 247.13 ± 17.15 minutes, which was considerably less than the 296.6 ± 21.7 minutes reported in the caudal block group (p < 0.001). The IINB group also showed a markedly lower requirement of rescue analgesia, with an overall analgesic intake of 815+253 milligrams as compared to 1063+388 milligrams in the caudal block group (p = 0.005). Also, the IINB group had fewer complications, and there were no incidences of a motor block and only one case of urinary retention. Conversely, caudal block group had motor block in 7, and urinary retention in 5 patients.CONCLUSION: Both caudal blocks and IINB provide effective postoperative analgesia in pediatric inguinal surgeries; however, IINB offers comparable pain relief with fewer complications and lower analgesic requirements, making it the safer and preferred technique.